(untitled) (Journal of Society of Surgeons of Nepal, 2023)
Symptomatic hepatic cysts are infrequent and their presentation with rupture leading to an hemoperitonium is even more uncommon. This case report illustrates the challenges associated with the diagnosis and management of a ruptured simple hepatic cyst. We report the case of 72-year-old female, a known case of liver cirrhosis, hypertension, diabetes mellitus, and cholelithiasis who presented to our center with features of acute abdomen and was diagnosed with the ruptured simple hepatic cyst. Deroofing and marsupialization of the cyst was performed. This case report emphasizes the significance of early recognition and a multidisciplinary approach in managing ruptured simple hepatic cysts. Heightened clinical awareness, coupled with advanced imaging techniques, is crucial for accurate diagnosis and timely intervention.